Can packaging transparency influence consumer food waste behavior? - Monireh Mahmoudi; Mina Mashayekhian (PLoS ONE, 2025)
Consumer food waste remains a significant concern in the United States, where approximately 40% of food goes uneaten, leading to major economic and environmental consequences. Packaging plays a key role in food preservation and consumer decision-making, yet little research has examined how specific packaging features, such as transparency, influence consumer waste behaviors. To explore this, we conducted a three-week framed field experiment involving approximately 200 university students, focusing on deli meat—a perishable item commonly wasted in U.S. households. In this study, students were recruited to purchase pre-packaged deli meat from the research team. To simulate opaque packaging conditions, we applied white duct tape externally to otherwise transparent packages. Participants picked up their food on a self-selected date and consumed it over time. They were instructed to return any food scraps between one and three weeks later, based on when they personally deemed the food unappealing. Food scraps were measured to examine the link between packaging transparency and food waste. Observed patterns suggest that transparency may exert two contrasting influences on consumer behavior. On one hand, transparency may foster a greater sense of perceived control by providing visual cues that enhance consumers’ confidence in monitoring food quality and planning consumption, potentially leading to reduced waste. On the other hand, transparency may lead to overconfidence, reducing consumers’ vigilance in checking food quality. This illusion of ongoing freshness could decrease the frequency of quality checks and delay initial inspections, ultimately increasing the risk of spoilage and waste. While the results did not reach statistical significance, they consistently revealed directional trends, supporting an exploratory interpretation of the behavioral mechanisms involved. Although these findings are exploratory, they offer valuable insights into how packaging transparency may paradoxically shape consumer behaviors, emphasizing the importance of tailoring packaging strategies to mitigate food waste.